Metropolitan ungovernability - Compans, Rose (Revista Brasileira de Estudos Urbanos e Regionais, 2015)
Although most of the population already live in metropolitan areas, in the Brazilian legal framework, there is still no appropriate legal ruling for managing these territories. The federal pact resulting from the Federal Constitution of 1988 established that it was at the prerogative of the states to create metropolitan regions, urban agglomerations and micro-regions, but did not attribute sufficient powers to them so they could conduct public functions of common interest (FPICs, in Portuguese), given the municipal autonomy likewise granted by the Constitution. In no other aspect does this legal conflict appear more evident than in territorial organization, since virtually all the instruments for the control of land use are of exclusively municipal competence. The purpose of this article is to discuss the possibilities of smoothing the way to an understanding on the limits of local autonomy in conurbations, thereby subordinating the “local” interest to the common interest, with regard to the regulating urban occupation. Therefore, we start with a brief analysis of the 1973 Law which set up the first metropolitan areas in Brazil, and thereby seek to identify advances and retrograde steps that the Constitution represented in relation to the division of powers between federal entities with respect to land management. Then, we investigate the role that post-1988 federal law reserves to metropolitan bodies in organizing, planning and carrying out FPICs in order to catch sight of windows of opportunity to bring them into force with regard to regulating the use of land. Finally, we discuss if the Statute of the Metropolis, which has recently been approved, provides the legal framework needed to overcome the antagonisms that criss-cross metropolitan governance.